(untitled) (Al-Academy, 2021)
Publications are generally considered an effective visual artistic means that addresses the recipient (the audience), with the functional, aesthetic and expressive dimensions they carry that contribute to spreading a diverse cultural awareness, especially those publications that are concerned with their media, promotional and organizational performance, as well as specific cultural events at specific times, in pursuit Access to renewable and elaborate designs to achieve the functional and aesthetic purpose, as the completed design and construction process is subject to many variations, whether this diversity is intellectual or technical, internal or external, and all of them may overlap to obtain a comprehensive system of artistic formation, that is, the design reaches its maximum expression On the content by achieving the highest levels of mastery, it is related to the extent of his observance and closeness to these techniques, so we find their reflections firmly in the mind of the individual, especially the designer artist who is influenced by everything that surrounds him, forming a cognitive system that is responsive and in harmony with these variables and is reflected in his perception, and then his performance is affected and influenced. The rest of the overhaul of the design structure.Based on the above, the researcher found that the problem of his research is summarized by the following question: What are the printing techniques and their role in enhancing the aesthetic dimension in digital printing?The researcher also reviewed in the theoretical framework that included: The first topic: the concept of technology. The second topic: repulsive technologies. The third topic: typographic elements and aesthetic impact.The indicators that resulted from the theoretical framework were extracted as a scientific material that the researcher reported in his research procedures, as the unit of analysis was determined, and this represented in considering each announcement as a unit of analysis as it carries an integrated communicative idea from which ideas can be developed through analysis. And the extent of its impact on the design structure.He concluded with the results and conclusion), including:1. The designer relied on fully occupying the design space with real images, and the company’s trademark was dominant within the design space for the advertisement, as in Model No. (1).2. The technical design development contributes to the product marketing process by keeping pace with the operational techniques that can establish outlets to show good design.The chapter concluded with recommendations and suggestions, and sources and references.